Developing a Web-Based Application to Support Student Behavior Monitoring in Vocational Education - Dahlan, Hesti; Sujaini, Herry; Basri, Muhammad; Aunurrahman; Salam, Urai (Jurnal Paedagogy, 2026)
This study aims to develop and implement a web-based student behavior monitoring application for Grade X students of Computer and Telecommunication Network Engineering (TJKT) at SMKN 1 Sambas and to analyze its impact on student behavior and learning outcomes. The research employed a Research and Development (R&D) method using the ADDIE model, encompassing the stages of needs analysis, design, development, implementation, and evaluation. The data analysis combined quantitative descriptive and qualitative approaches. Quantitative data obtained from expert validation sheets and questionnaires were analyzed using percentage-based descriptive statistics to determine the feasibility and practicality of the developed application. Meanwhile, qualitative data derived from observations and documentation were analyzed through data reduction, data display, and conclusion drawing to support the interpretation of the findings. Data were collected through observations, questionnaires, and documentation, involving teachers, class advisors, parents, and students. The expert validation results indicated that the application is highly feasible, with scores of 88.31% from content experts, 88.94% from media experts, and 86.48% from technology experts. Practicality testing by teachers and parents also categorized the application as highly practical, with scores of 83.51% and 84.94%, respectively. Behavioral evaluation showed significant improvement, with teacher-led interventions reaching 81.27% (good category) and student self-interventions 85.45% (very good category). Furthermore, academic outcomes improved significantly, with the class average increasing from 70 to 79. The t-test analysis yielded a p-value of 0.000 (p < 0.05), indicating that the application effectively enhances both student discipline and academic performance. In conclusion, the developed web-based application is valid, practical, and effective in improving student behavior and learning outcomes.